Population Migration and The Challenges of Economic Growth in North Sumatera in Year (1988-2020) - Zulkarnain Nasution; Muhammad Ali Al Ihsan (Journal of Social Science, 2021)
Population increase has the impact on demographic transition (changes in population structure). Indonesia is entering the demographic bonus period, there is the increase in the percentage of the working age population. According to theory, population can affect economic growth (in this study the effect on gross domestic product or GDP). One of the demographic components that affect population composition is population mobility or migration. This study used migration, risk migration and dependency ratios to show the latest patterns / trends of population mobility (last 20 years). The results showed that the variables in this study had a positive and negative effect on GDP growth. Of the three variables, the greatest influence is given by percentage of dependency ratio variable. The results of this study showed that migration and risk migration had negative impact on economic growth while the dependency ratio had a positive impact on economic growth. North Sumatra must be optimistic to increase economic growth by utilizing components that can boost the economy and one of them is the dependency ratio.